2019
DOI: 10.1016/j.neuropharm.2018.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Development of the MAM model of schizophrenia in mice: Sex similarities and differences of hippocampal and prefrontal cortical function

Abstract: Schizophrenia is a debilitating disorder with complex and unclarified etiological factors. Sex differences have been observed in humans but animal models have only focused on male subjects. In this study, we report the establishment of the neurodevelopmental MAM model of schizophrenia in mice and compare the schizotypic-like characteristics and cognitive function in both sexes. Pregnant mice were injected with 26mg/kg(i.p.) of Methylazoxy-methanol acetate (MAM) or saline (5ml/kg) on gestational day (GD) 16 (MA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 107 publications
7
23
0
Order By: Relevance
“…The neurodevelopmental MAM16 mouse model of SZ revealed sex differences in PFC-dependent cognitive function, PFC proteome, and PV expression in the PFC and the HPC (Chalkiadaki et al, 2019). Moreover, prenatal PolyI: C treatment led to PPI sex-specific deficits (O'Leary et al, 2014;Ratnayake et al, 2014), to male-specific impairments in fear conditioning (Vorhees et al, 2012), in set-shifting task (Zhang et al, 2012), and in recognition memory test (Howland et al, 2012) as well as to female-specific dysfunction in spatial memory (O'Leary et al, 2014).…”
Section: Sex Differences In Sz Animal Modelsmentioning
confidence: 99%
“…The neurodevelopmental MAM16 mouse model of SZ revealed sex differences in PFC-dependent cognitive function, PFC proteome, and PV expression in the PFC and the HPC (Chalkiadaki et al, 2019). Moreover, prenatal PolyI: C treatment led to PPI sex-specific deficits (O'Leary et al, 2014;Ratnayake et al, 2014), to male-specific impairments in fear conditioning (Vorhees et al, 2012), in set-shifting task (Zhang et al, 2012), and in recognition memory test (Howland et al, 2012) as well as to female-specific dysfunction in spatial memory (O'Leary et al, 2014).…”
Section: Sex Differences In Sz Animal Modelsmentioning
confidence: 99%
“…Patients with psychosis display hyper-sensitivity to psychomotor stimulants which can be modeled in rats by measuring locomotor activity before and after administration of the NMDA antagonist, MK-801 10,41,43 . Consistent with previous literature 44 , stress/vehicle rats showed an increase in locomotor activity at baseline, compared to control/vehicle rats ( Fig.…”
Section: Mk-801 Induced Locomotor Activity Increases After Stress Butmentioning
confidence: 99%
“…In the prenatal immune challenge model of SZ in mice, for example, distinct sex differences were found in microglial distribution, process arborization, oxidative stress, synaptic function, and expression of inflammatory genes that may be relevant to the increased incidence of severe SZ in males [ 48 ]. In the MAM model of SZ in mice, sex differences have been reported not only in neuronal activity, but also in the expression of regulatory proteins, primarily those involved in glutamatergic signaling in the prefrontal cortex [ 49 ]. While glutamatergic transmission drives excitation in cortical circuits, inhibition from gamma aminobutyric acid (GABA)ergic interneurons plays a key role in regulating excitability of pyramidal neurons in order to generate synchronized firing patterns required for efficient communication between neuronal ensembles [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a decrease in parvalbumin-positive interneurons, in line with those observed in human SZ patients, in both MAM-treated male and female rats has been shown [ 10 , 52 ]. Conversely, Chalkiadaki et al [ 49 ] found that MAM exposure decreased the expression of parvalbumin in male but not in female mice, and that only male mice exhibited prefrontal cortical deficits in activity, a discrepancy that may be explained by the different species employed.…”
Section: Discussionmentioning
confidence: 99%